Colletotrichum species associated with atemoya anthracnose in northeast Brazil - Santos, Jockeliny Mayara Câmara dos; Costa, Jaqueline Figueredo de Oliveira; Silva, Jackeline Laurentino da; Lima, Tiago Silva; Santos, Taciana Ferreira dos; Assunção , Iraildes Pereira; Lima, Gaus Silvestre de Andrade (Comunicata Scientiae, 2024)
Anthracnose, caused by Colletotrichum spp., is an important disease of atemoya that can infect and cause damage to different plant organs. The symptoms include foliar anthracnose, flower abortion, branch tip bleaching, and necrotic lesions on fruits. Knowing the etiology of this disease is essential for properly developing management strategies. Therefore, this study aimed to identify Colletotrichum species associated with atemoya in the Northeast region of Brazil, based on multi-locus phylogeny and morphological analyses, to better understand the etiology of anthracnose in this plant species. The Colletotrichum isolates were obtained from symptomatic leaves and branches of atemoya collected in commercial fields in Vitória da Conquista (Bahia), Palmeira dos Índios and Rio Largo (Alagoas), located in northeast Brazil. The initial analysis of the partial sequences of the GAPDH gene was performed with nineteen Colletotrichum isolates obtained from leaves and branches of atemoya trees with typical anthracnose symptoms. Seventeen isolates were grouped in the gloeosporioides complex and two in the boninense complex. Therefore, eleven isolates were submitted to concatenated phylogenetic analyses with the genes GAPDH, TUB2, and ITS region of the rDNA to confirm the identity of the isolates at the species level. The species C. theobromicola, C. siamense, C. fructicola and C. karstii were identified and are associated with atemoya anthracnose in the Northeast region of Brazil.